Education Policy Recommendations In Addressing Digital Transformation And Access Inequality In Indonesia: A Public Administration Perspective - Rindawati, Septi; Saputra, Dhian Gita; Supriadi, Supriadi (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study examines education policy in Indonesia within the context of digital transformation and governance challenges. Education is positioned as a strategic sector in national development, playing a vital role in improving human resource quality and supporting economic growth. However, despite strong regulatory frameworks and substantial government commitment, the implementation of education policy still faces significant challenges, including disparities in infrastructure, unequal access between regions, and low digital competency among educators. The study highlights a persistent gap between policy formulation and implementation, which is influenced by leadership, institutional capacity, and stakeholder involvement. This research employs a qualitative approach using a literature review method, analyzing data from academic journals, policy documents, and relevant literature. The findings reveal that digital transformation offers significant opportunities to enhance accessibility, flexibility, and learning quality through technology integration. However, it also poses risks such as widening the digital divide if not managed through inclusive and adaptive policies. SWOT analysis indicates that Indonesia’s education policy has strong potential but requires strategic interventions, including strengthening digital infrastructure, improving teacher competencies, and enhancing governance systems. The study proposes policy recommendations based on SWOT strategies, emphasizing the importance of integrating technology with curriculum and management systems, strengthening multi-stakeholder collaboration, implementing context-based policies, and ensuring data-driven decision-making. In addition, efforts to reduce digital inequality, enhance leadership capacity, and promote inclusive digital literacy programs are crucial for sustainable reform. Overall, education policy in Indonesia must shift toward a more adaptive, collaborative, and implementation-oriented approach to effectively address global challenges and achieve equitable, high-quality, and sustainable education.